Thyroid Autoantibodies in the Cerebrospinal Fluid of Subjects with and without Thyroid Disease: Implications for Hashimoto's Encephalopathy. (21st December 2015) - Ilias, Ioannis; Karagiorga, Vasiliki; Paraskevas, George; Bougea, Anastasia; Bourbouli, Mara; Pappa, Athina; Nikopoulou, Stamatina; Kapaki, Elisabeth
Abstract : Introduction . Plasma antithyroid peroxidase (anti-TPO) and anti-thyroglobulin antibodies (anti-Tg) are widely used in the diagnosis of autoimmune thyroiditis. No research has compared anti-TPO and anti-Tg both in plasma and cerebrospinal fluid (CSF) of healthy individuals vis-à-vis patients with thyroid disease. Methods . We measured anti-TPO and anti-Tg antibodies in plasma and CSF in nine subjects (mean age ± SD: 73 ± 6 years) with hypothyroidism and nine subjects (mean age ± SD: 73 ± 8 years) without thyroid disease. Results . The concentration of anti-TPO autoantibodies in CSF was very low compared to plasma in both subjects with thyroid and without thyroid disease (P = 0.007 ). CSF anti-Tg autoantibodies titers were very low compared to the plasma in subjects with thyroid disease (P = 0.004 ), whereas, in subjects without thyroid disease, this difference did not reach statistical significance (P = 0.063 ). Conclusions . Thyroid autoantibodies levels were low in plasma and CSF; we did not observe any transfer of thyroid autoantibodies from the peripheral blood to the CSF. Therefore, regarding Hashimoto's encephalopathy, where elevated antithyroid autoantibodies are often measured in blood, it is more likely that thyroiditis and encephalopathy represent nonspecific, but distinct, events of an aggressive immune system.